Design and development of POCN-pincer palladium catalysts for C-H bond arylation of azoles with aryl iodides - Khake, Shrikant M.; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2014)
{Well-defined and efficient POCN-ligated palladium complexes have been developed for the direct C H bond arylation of azoles with aryl iodides. The phosphinite-amine pincer ligands 1-(R2PO)-C6H4-3-((CH2NPr2)-Pr-i) 1R2POCNIPr2-H; R = `Pr (1a)

Metal-free regioselective C-3 acetoxylation of N-substituted indoles: crucial impact of nitrogen-substituent - Soni, Vineeta; Patel, Ulhas N.; Punji, Benudhar (RSC Advances, 2015)
A metal-free method for the regioselective C-3 acetoxylation of the N-substituted indoles with PhI(OAc)(2) is described under mild reaction conditions. This method tolerates a broad range of functional groups with moderate to good yields. The pi-electron-deficient aryl-substituents on the N-atom of indoles and the acidic reaction medium remarkably favor C-3 acetoxylation.

Unified strategy for nickel-catalyzed C-2 Alkylation of indoles through chelation assistance - Soni, Vineeta; Jagtap, Rahul A.; Gonnade, Rajesh G.; Punji, Benudhar (ACS Catalysis, 2016)
A nickel-catalyzed direct C-2 alkylation of indoles through monodentate-chelation assistance has been described. This reaction proceeds via an unusual strategy by the use of a well-designed and defined (quinolinyl)amido–nickel catalyst, [{κN,κN,κN-Et2NCH2C(O)(μ-N)C9H6N}Ni(OAc)], providing a solution to the limitations associated with bidentate-chelate auxiliaries. The method allows coupling of indoles with various unactivated primary and secondary alkyl halides with ample substrate scope. This uniquely strategized alkylation proceeded through crucial C–H activation and via an alkyl radical intermediate. The reaction by this approach represents a rare example of Ni-catalyzed monodentate-chelate-assisted C–H functionalization.

Development of (quinolinyl)amido-based pincer palladium complexes: a robust and phosphine-free catalyst system for C–H arylation of benzothiazoles - Pandiri, Hanumanprasad; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2017)
(Quinolinyl)amido-ligated palladium(II) complexes have been synthesized and applied in the catalytic C–H bond arylation of benzothiazoles. The tridentate ligand precursors R2N-C(O)CH2-(NH)-C9H6N [(R2NNN8-Q)–H; R2N = morpholinyl, Me-N-piperazinyl] and the pincer palladium complexes [κN,κN,κN-{R2N-C(O)CH2-(μ-N)-C9H6N}]PdX [(R2NNN8-Q)PdX {R2N = Et2N, morpholinyl, Me-N-piperazinyl; X = OAc or Cl}] were efficiently synthesized, and characterized by various analytical techniques. The iodo derivative (Et2NNN8-Q)PdI was obtained in excellent yield by the treatment of the complex (Et2NNN8-Q)PdCl with KI. The molecular structures of complexes (Et2NNN8-Q)Pd(OAc) (2a), (Et2NNN8-Q)PdCl (3a) and (Et2NNN8-Q)PdI (4a) were elucidated by X-ray crystallography. Complex 3a was found to be the most efficient catalyst for direct C–H bond arylation of substituted benzothiazoles with diverse aryl iodides using a mild base, K2CO3. The working catalyst system 3a is highly robust and can be recycled and reused several times for the arylation of benzothiazole without loss of catalytic activity. Preliminary mechanistic investigations using controlled studies and kinetic analysis have been performed, which greatly support a molecular mechanism for the arylation.

Expeditious and solvent-free nickel-catalyzed C−H arylation of arenes and indoles - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2017)
An efficient solvent-free nickel-catalyzed method for C−H bond arylation of arenes and indoles has been developed, which proceeds expeditiously through chelation assistance. The reaction is highly selective for mono-arylation and tolerates sensitive and structurally diverse functionalities, such as halides, ethers, amines, indole, pyrrole and carbazole. This reaction represents the first example of a nickel-catalyzed C−H arylation by monochelate assistance and symbolizes a rare precedent in solvent-free C−H arylation. Mechanistic investigations by various controlled reactions, kinetic studies, and deuterium labeling experiments suggest that the arylation follows a single electron transfer (SET) pathway involving the turnover-limiting C−H nickelation process.

General nickel-catalyzed method for C-H bond alkynylation of heteroarenes through chelation assistance - Punji, Benudhar; Khake, Shrikant manmathappa; Soni, Vineeta; Gonnade, Rajesh Ghanshyam (Chemistry - A European Journal, 2017)
A general nickel-catalyzed method for the alkynylation of heteroarenes through monodentate chelation assistance is described. Many heterocycles, including indoles, pyrroles, imidazoles and pyrazole, efficiently coupled with (triisopropylsilyl)alkynyl bromide, and synthetically important functional groups, such as halides, ether, nitrile, nitro were tolerated. Synthetic applicability of this Ni-catalyzed method is demonstrated by the removal of triisopropylsilyl (-SiiPr₃) group, and further functionalization into triazolyl, benzofuranyl and alkynyl arene derivatives. Preliminary mechanistic investigations on the alkynylation of indole suggest that the reaction proceeds through kinetically relevant C-H activation and follows the two-electron redox pathway. A catalytically competent Ni-species, [(Phen)₃Ni].NiBr₄ has been isolated and structurally characterized.

Palladacycles for directed and nondirected C H bond functionalization of (Hetero)arenes - Soni, Vineeta; Punji, Benudhar (Strategies for palladium-catalyzed non-directed and directed C-H bond functionalization, 2017)
Application of palladacycle complexes in catalytic organic transformation is rapidly expanding. This chapter is mainly focused on the use of palladacycle precatalysts in CH bond functionalizations, as well as an overview of palladacycle intermediates in directed CH bond functionalization reactions. The described palladacycle precatalysts are more efficient and more selective than the traditional palladium complexes for CH bond functionalization processes. The second part of the chapter summarizes the involvement of palladacycle intermediates in various directed CH bond functionalizations that are proposed with experimental evidence. Some of the palladacycle intermediates described are shown to be competent as catalyst precursors. It has been demonstrated that the formation of palladacycle (precatalyst or intermediate) makes the CH functionalization process more facile, because of the high stability associated with palladacycles.

Nickel-catalyzed regioselective C(2)-H difluoroalkylation of indoles with difluoroalkyl bromides - Soni, Vineeta; Sharma, Dipesh M.; Punji, Benudhar (Chemistry-An Asian Journal, 2018)
Regioselective C(2)-H difluoroalkylation of C-3 unsubstituted indoles with commonly available fluoroalkyl bromides is successfully achieved employing a simple nickel catalyst system, (DME)NiCl2/Xantphos. This methodology shows excellent regioselectivity and exhibits a broad substrate scope. Various functional groups, such as -OMe, -F, and -Br, are tolerated on the indole backbone to give the difluoroalkylated products in moderate to good yields. Preliminary mechanistic findings demonstrate that the reaction is homogeneous in nature and involves a radical manifold. Synthetic utility of this nickel-catalyzed method is demonstrated by synthesizing melatonin receptor antagonist Luzindole derivative.

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides